Assessment of land-use changes and their impacts on ecosystem services in two Slovenian rural landscapes - Ribeiro, Daniela; Šmid Hribar, Mateja (Acta geographica Slovenica, 2019)
This study shows the link between land use, landscape changes, and ecosystem services. Two pilot areas were investigated for how land use changes from 1824 to 2013 affect the provision of ecosystem services. It was found that low-intensity managed traditional land use is disappearing due to the intensification of agricultural production on the one hand, and the retreat of agriculture from unfavorable areas on the other hand. However, such traditional land use contributes to more diverse and more numerous ecosystem services and helps preserve the cultural landscape. Therefore, intensification and overgrowth should be restricted, and less intensive agriculture should be encouraged. The approach presented can be used as a support tool for decision-making in managing and governing landscapes.